A poly(L‐lactic acid) monofilament with high mechanical properties for application in biodegradable biliary stents. Issue 2 (27th July 2020) - Tian, Yuan; Zhang, Jing; Cheng, Jie; Wu, Gensheng; Zhang, Yi; Ni, Zhonghua; Zhao, Gutian
Abstract: In this article, a poly(L‐lactic acid) (PLLA) monofilament with high mechanical properties which can be used to construct biodegradable biliary stents (BBS) is prepared. Compared with a commercial polydioxanone (PDO) suture, the PLLA monofilament has much higher Young's modulus. As a result, chronic outward force (COF) of the stent braided by PLLA monofilament is more than three times higher than that of the stent braided by PDO suture. Furthermore, by physicochemical indexes characterizations, it is acceptable that the PLLA monofilament has stable Young's modulus and higher elongation at break without brittle fracture risk during degradation in bile. In contrast, although PDO suture can also maintain Young's modulus well during degradation, its elongation at break is attenuated rapidly, which shows a high brittle fracture risk. These results indicate that PLLA monofilament is more suitable for constructing BBS with high COF, which are promising in treating more complex biliary strictures that need longer support time. Abstract : Young's modulus of the monofilament has a significant effect on the radial force of the braided stent. Compared with a commercial polydioxanone (PDO) suture, the poly(L‐lactic acid) (PLLA) monofilament with the same diameter has much higher Young's modulus. Therefore, the chronic outward force of the stent braided by PLLA monofilament is more than three times higher than that of the stent braided by PDO suture into the same structure.